IMPLEMENTASI MODEL PEMBELAJARAN INTEGRASI DALAM UPAYA PENINGKATAN KREATIVITAS MAHASISWA - Rosnelli Rosnelli; Siti Zulfa Yuzni (JURNAL TEMATIK, 2021)
This study aims to implement an integrated learning model in an effort to improve student learning outcomes. Another research objective is to determine the impact of the implementation of the integration learning model on student creativity. The research method used is quasi-experimental. Collecting data through a questionnaire to capture the impact of learning and the impact of the implementation of the integration model accompaniment. To see the learning outcomes used tests. To see the condition of higher learning outcomes used t test. The results showed that student learning outcomes using the integration learning model were higher when compared to student learning outcomes using the expository learning model which included conducting experiments in the workshop. The impact of the implementation of the integration learning model is that there is an increase in learning outcomes, besides the accompanying impact is the growth of creativity, selfdetermination, and student motivation in producing innovative products based on the specifications of the study program they choose.